KEEFEKTIFAN RENDAM KAKI AIR HANGAT DALAM PENURUNAN SUHU TUBUH PADA ANAK DEMAM 6 – 12 TAHUN - Dian Nur Wulanningrum; Sherli Ardianti (Journal of Advanced Nursing and Health Sciences, 2021)
Fever is a form of reaction or natural process of the body against bacteria, viruses or bacteria as evidence of the body fighting infection. Fever is one of the symptoms that appear in a disease in a person's body, both children and adults. Fever often occurs in children, especially children 6-12 years. So that parents as the closest people to children need to have knowledge about how to handle problems appropriately. And health workers, especially nurses, need to know the right way of handling according to the results of research in providing treatment actions. One of the methods of treatment in question is soaking the feet in warm water. This study aims to determine the effectiveness of warm foot baths on reducing body temperature in children 6-12 years old. This study uses a quasi-experimental research design with a pre-test and post-test approach without control group design. Analysis of the data in this study using the Wilcoxon test. The results of this study indicate that the p value is 0.000 (p value <0.05), meaning that there is a decrease in body temperature after a warm foot soak. The conclusion of this study is that warm water foot soaks are effective in reducing body temperature in children 6-12 years old.